2022
DOI: 10.1038/s41598-021-04027-8
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of gene expression by the APP family in the adult cerebral cortex

Abstract: Amyloid precursor protein (APP) is associated with both familial and sporadic forms of Alzheimer’s disease. APP has two homologs, amyloid precursor-like protein 1 and 2 (APLP1 and APLP2), and they have functional redundancy. APP intracellular c-terminal domain (AICD), produced by sequential α- or β- and γ-secretase cleavages, is thought to control gene expression, similarly as the ICD of Notch. To investigate the role of APP family in transcriptional regulation, we examined gene expression changes in the cereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Table 3 shows Metagene 9 is involved in hsa04974:protein digestion and absorption as the most significant (p-value <0.05) KEGG pathway. In a recent study, protein digestion and absorption pathway was reported as one of the most significant pathway was in diabetic complications in the adult neocortex [ 77 ]. Table 3 further lists the significant enrichments of Metagene 9 reported GO terms in biological processes (BP) is in brain development (GO:0007420) [ 78 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Table 3 shows Metagene 9 is involved in hsa04974:protein digestion and absorption as the most significant (p-value <0.05) KEGG pathway. In a recent study, protein digestion and absorption pathway was reported as one of the most significant pathway was in diabetic complications in the adult neocortex [ 77 ]. Table 3 further lists the significant enrichments of Metagene 9 reported GO terms in biological processes (BP) is in brain development (GO:0007420) [ 78 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…The two APP homologues APLP1 and APLP2 are similarly processed by the same secretases, producing the intracellular fragments APLP-Intracellular Domain 1 (ALID1) and ALID2, respectively [ 52 ]. Similarly to AICD, ALID1 and ALID2 have been proposed to play a functional role as transcriptional regulators [ 53 ], although the validity of these speculations is still controversial due to the lack of adequate animal models.…”
Section: Amyloid Precursor Protein: Structure Expression and Processingmentioning
confidence: 99%
“…These findings highlight the importance of the close association of working among all three proteins under healthy conditions. 26 In treating complex diseases like A.D., one major challenge is the lack of defined objective diagnostic criteria and robust biological markers of A.D. 27 Other issues are the failure of drugs due to their adverse side effects. For example, Gantenerumab causes micro hemorrhage; Gamma Gard causes headache and nausea, Scyllo-inositol causes depression, etc.…”
Section: Introductionmentioning
confidence: 99%
“…These findings highlight the importance of the close association of working among all three proteins under healthy conditions. 26…”
Section: Introductionmentioning
confidence: 99%